Analisis Dan Evaluasi Proses Bisnis Menggunakan Metode Failure Mode And Effect Analysis (Fmea) (Studi Pada Dinas Perpustakaan Dan Kearsipan Kota Batu) - Hisam Rahman Hakim; Aditya Rachmadi; Alfi Nur Rusydi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The Office of Library and Archives of Batu City is an agency that has the main task and function of organizing public services in the field of literature and archives in the Batu City area. There are several problems that occur in the business processes that are carried out, especially in library services, such as getting complaints from library visitors, unfulfilled visitor requests and the loss of several collections of reading materials. Due to this, it is necessary to evaluate business processes to find out more about problems and find solutions. The initial step taken was to identify the ongoing business processes using the